Seeking Culturally Safe Developmental Evaluation: Supporting the Shift in Services for Indigenous Children - Natasha Blanchet-Cohen; Pascale Geoffroy; Luz Luz Marina Hoyos (The Evaluation Center at Western Michigan University, 2018)
Background: Evaluation methods based on western frameworks that disregard Indigenous peoples' worldviews and are imposed and implemented by outsiders are problematic for Indigenous communities.   Purpose: The article presents the experience of using developmental evaluation (DE) in supporting a shift in pre- and post-natal care programming for Indigenous mothers and their young children.   Setting: Indigenous peoples living in urban areas in Quebec often feel unwelcome mainstream services, resulting in under-use. A history of colonization in Canada has resulted in a loss of Indigenous child-rearing practices   Intervention: The study was carried out in the context of a three-year initiative aimed at strengthening the abilities of pregnant women, mothers, fathers, extended family, community, and practitioners to create conditions for the holistic development of themselves and their children. The goal was to create new knowledge through activities focused on promoting perinatal care and psychosocial adaptability. Cultural safety, an ecosystemic view of child development, and social innovation guided the approach to the intervention.   Research Design:  A case study approach was used to make sense of and describe the "how to" of the DE.   Data Collection and Analysis: Multiple methods of data collection informed the case study, including observation, field notes, interviews, and participatory evaluation activities.   Findings: The article sheds light on DE as a culturally safe and participatory practice that is compatible with Indigenous perspectives and contributes to supporting the transformation in services provided to Indigenous communities. We present building relationships, creating safe spaces for reflection and dialogue, questioning fundamentals, and co-creation as critical components of culturally safe DE, enabling development and a paradigm shift.   Keywords: developmental evaluation; indigenous; child-rearing; case study; cultural safety.